Efficacy of Oxygen Fluid (blue®m) on Human Gingival Fibroblast Viability, Proliferation and Inflammatory Cytokine Expression: An In Vitro Study - Rhodanne Nicole A. Lambarte; Amani M. Basudan; Marwa Y. Shaheen; Terrence S. Sumague; Fatemah M. AlAhmari; Najla M. BinShwish; Abeer S. Alzawawi; Abdurahman A. Niazy; Mohammad A. Alfhili; Hamdan S. Alghamdi (Applied Sciences)
Human gingival fibroblasts (HGnFs) play crucial roles in periodontal wound healing. This in vitro study examined the impact of varying concentrations of topical oxygen fluid (blue®m) on HGnF morphology, viability, proliferation, oxidative stress and pro-inflammatory cytokine production. The attempt was to underscore the potential of blue®m as a less cytotoxic alternative to chlorhexidine in the context of tissue-regeneration improvement. Primary HGnF cell cultures were subjected to oxygen fluid (blue®m) at concentrations of 0.6, 1.2 and 2.4% for a duration of 1 min. The positive control was 0.12% chlorhexidine. Cell morphology as well as actin cytoskeleton were assessed using microscopy and immunofluorescence staining. Cell viability and proliferation were assessed through AlamarBlue and trypan blue assays at 1, 2, 7, 10 and 14 days. Levels of reactive oxygen species (ROS) were quantified using DCFH-DA assay. Pro-inflammatory cytokines (IL-1β, IL-6, TNF-α, MMP-8 and TIMP-1) were assessed through ELISA. HGnF morphology and actin structure were preserved at all oxygen fluid concentrations. Cell viability and proliferation were significantly higher in the 0.6% and 1.2% groups than in the control and chlorhexidine groups (p ≤ 0.05). ROS levels were low at 0.6% and 1.2%, but increased at 2.4% and with chlorhexidine (p ≤ 0.05). Oxygen treatment reduced IL-1β, IL-6, TNF-α and TIMP-1 expression, while MMP-8 levels increased. Chlorhexidine significantly upregulated the expression of all proinflammatory cytokines (p ≤ 0.01). Oxygen fluid (blue®m) therapy improves the viability and proliferation of gingival fibroblasts and offers anti-inflammatory and preliminary antioxidative effects at the cellular level, especially at lower concentrations (0.6% and 1.2%), indicating potential application in periodontal wound management, subject to clinical validation.